PCL/PHBV blended three dimensional scaffolds fabricated by fused deposition modeling and responses of chondrocytes to the scaffolds. Issue 5 (28th March 2016) - Kosorn, Wasana; Sakulsumbat, Morakot; Uppanan, Paweena; Kaewkong, Pakkanun; Chantaweroad, Surapol; Jitsaard, Jaturong; Sitthiseripratip, Kriskrai; Janvikul, Wanida
Abstract: In this study, poly(ε‐caprolactone)/poly(3‐hydroxybutyrate‐ co −3‐hydroxyvalerate) (PCL/PHBV) blended porous scaffolds were fabricated by fused deposition modeling (FDM). PCL/PHBV filaments, initially prepared at different weight ratios, that is, 100/0, 75/25, 50/50, and 25/75, were fabricated by the lay‐down pattern of 0/90/45/135° to obtain scaffolds with dimension of 6.0 × 6.0 × 2.5 mm 3 and average filament diameters and channel sizes in the ranges of 370–390 µm and 190–210 µm, respectively. To enhance the surface hydrophilicity of the materials, the scaffolds were subsequently subjected to a low pressure oxygen plasma treatment. The untreated and plasma‐treated scaffolds were comparatively characterized, in terms of surface properties, mechanical strength, and biological properties. From SEM, AFM, water contact angle, and XPS results, the surface roughness, wettability, and hydrophilicity of the blended scaffolds were found to be enhanced after plasma treatment, while the compressive strength of the scaffolds was scarcely changed. It was, however, found to increase with an increasing content of PHBV incorporated. The porcine chondrocytes exhibited higher proliferative capacity and chondrogenic potential when being cultured on the scaffolds with greater PHBV contents, especially when they were plasma‐treated. The PCL/PHBV scaffolds were proven to possess good physical, mechanical, and biological properties that could be appropriately used in articular cartilage regeneration. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1141–1150, 2017.